Ḥayāt-i Jāvīd - Ḥālī, Ḵẖvājah Al̤tāf Ḥusain, 1837-1914 (Silsilah-yi ma̤tbūʻāt-i Anjuman Taraqqī-yi Urdū, Hind, 1939)
On the life of Sir Sayyid Aḥmad Ḵẖāṉ, 1817-1898, Indian statesman and founder of the Aligarh Muslim University.